Physiotherapists’ attitudes and beliefs about low back pain influence their clinical decisions and advice - Christe, Guillaume; Nzamba, Jessica; Desarzens, Ludovic; Leuba, Arnaud; Darlow, Ben; Pichonnaz, Claude (Musculoskeletal science & practice, 2021)
Physiotherapists' biomedical orientation influences the implementation of evidenced-based care for low back pain (LBP) management. However, information on physiotherapists’ own beliefs about their back and LBP and the influence of these on clinical decisions and advice is lacking. To identify attitudes and beliefs about LBP among physiotherapists and to analyse the association of these beliefs with physiotherapists’ individual characteristics and clinical decisions and advice. Cross-sectional survey. Attitudes and beliefs about LBP were measured with the Back-Pain Attitudes Questionnaire (Back-PAQ) among French-speaking Swiss physiotherapists. Physiotherapists’ clinical decisions and advice were assessed with a clinical vignette to determine their association with the Back-PAQ score. The study included 288 physiotherapists. The mean Back-PAQ score (82.7; SD 17.2) indicated the presence of helpful beliefs in general, but unhelpful beliefs in relation to back protection and the special nature of LBP (nature of pain, impact, complexity) were frequently identified. Individual characteristics explained 17% of the Back-PAQ score. Unhelpful beliefs were associated with clinical decisions toward back protection and movement avoidance (r = - 0.47, p < 0.001). While helpful beliefs and guidelines consistent decisions were generally identified, unhelpful beliefs about back protection and the special nature of LBP were frequently present among physiotherapists. These unhelpful beliefs were associated with less optimal clinical decisions. Educational approaches should challenge unhelpful beliefs and empower physiotherapists to provide explanations and management that increases patients’ confidence in the back. Future research should investigate the effect of educational strategies on implementation of best practice for LBP management. •Beliefs that the back needs to be protected and that back pain is special were prevalent.•More years' experience or current LBP were associated with more unhelpful beliefs.•Physiotherapists appeared providing conflicting advice to both use and protect the back.•Unhelpful beliefs were associated with guideline-inconsistent clinical decisions.